«Trista è tal arte e tristo quel che spende / tutto il suo tempo in opra così vile»: edizione critica e commento dell’Alfabeto de’ giuocatori di Giulio Cesare Croce - Camesasca, Gloria (Italianistica Debreceniensis, 2018)
Giulio Cesare Croce (1550-1609) was a polygraph who composed several poetical works that describe the daily life of the Bolognese people. This paper examines Alfabeto de’ giuocatori, a poem dedicated to the theme of the game and of the vices and virtues of the players. The author analyzes the poem and discusses the transmission of the text and philological variants. The article is concluded by the critical edition and the commentary (regarding philological, linguistic, lessical and literary aspects).